Digital spectrometer. A proposal to build a Modern Physics experiment for remote learning (Research, Society and Development, 2021)
With the emergence of the Covid 19 pandemic, teaching suffered a very big shock, which made teachers look to technology for solutions for teaching. Technologies started to be considered as the only option to teach in times of confinement and started to be more present in the daily life of the teacher, mainly to replace the experimental activities developed in-person in higher education or to provide remote activities for basic education. In this context, this work presents the stages of construction of a digital spectrometer from reused materials from electronic equipment scrap, CCD camera, and media such as used CDs or DVDs, in addition to the Theremino software, which is free for data acquisition, visualization real-time and post-analysis. The experiment built was conceived to use in experimental classes in remote and/or in-person format in multidisciplinary activities that involve the study of the electromagnetic spectrum of different radiation sources and the phenomena of interaction with matter. The electromagnetic spectrum provides a wealth of information in research in the fields of astronomy, physics, chemistry, and biology. Its study is also very significant in the teaching of physics and astronomy, as it allows discussing various physical phenomena in the daily lives of students, which involve the behavior of radiation at different wavelengths. The digital spectrometer presented is low-cost equipment and an interesting tool to help students understand the behavior of electromagnetic radiation at different wavelengths and the importance of electromagnetic radiation in everyday applications, such as the need to use a filter to technological phenomena such as the photoelectric effect in the interaction of radiation with semiconductor devices.